07/20/2015-07/24/2015 2015
DOI: 10.7551/978-0-262-33027-5-ch064
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Compositional Language in a Population of Iterated Learners

Abstract: Iterated learning takes place when the input into a particular individual's learning process is itself the output of another individual's learning process. This is an important feature to capture when investigating human language change, or the dynamics of culturally learned behaviours in general. Over the last fifteen years, the Iterated Learning Model (ILM) has been used to shed light on how the population-level characteristics of learned communication arise. However, until now each iteration of the model ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…It is an empirical question whether the particular ranking of grammars in terms of simplicity that we can derive from this particular representation matches precisely the ranking that applies in the case of real language learners, but we are confident that the crucial distinction between degenerate < compositional < holistic is correct. This matches behavior of participants in the lab (Kirby et al, 2015 ) and broadly similar results are found in both connectionist and symbolic models of iterated learning (Kirby and Hurford, 2002 ; Brace et al, 2015 ).…”
supporting
confidence: 82%
“…It is an empirical question whether the particular ranking of grammars in terms of simplicity that we can derive from this particular representation matches precisely the ranking that applies in the case of real language learners, but we are confident that the crucial distinction between degenerate < compositional < holistic is correct. This matches behavior of participants in the lab (Kirby et al, 2015 ) and broadly similar results are found in both connectionist and symbolic models of iterated learning (Kirby and Hurford, 2002 ; Brace et al, 2015 ).…”
supporting
confidence: 82%
“…This supports other work that has demonstrated a link between the linguistic bottleneck and the number of linguistic tutors (Brace et al, 2015). Indeed, the behaviour seen in Figure 7 indicates that the factors underpinning the cultural transmission of language change and linguistic variation are perhaps too complicated to be understood by analysing the nature of just inter-and intra-generational transmission; and that further research into linguistic change should focus on the nature of the social network the underpins linguistic populations (Wichmann and Holman, 2009;Lupyan and Dale, 2010;Reitter and Lebiere, 2010;Milroy, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…A series of computer-based simulations that use the method of iterated learning have shown that the linguistic bottleneck is crucially important in regards to whether or not language can be successfully passed from one generation to the next and, in situations where this transmission can be achieved successfully, show that it is also crucial to the linguistic structure that arises (Kirby, 2002b,a;Kirby and Hurford, 2002;Kirby et al, 2014;Smith, 2002;Smith et al, 2003;Brace et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of computer-based simulations that use the method of iterated learning have shown that the linguistic bottleneck is crucially important in regards to whether or not language can be successfully passed from one generation to the next and, in situations where this transmission can be achieved successfully, show that it is also crucial to the linguistic structure that arises (Kirby, 2002b,a;Kirby and Hurford, 2002;Kirby et al, 2014;Smith, 2002;Smith et al, 2003;Brace et al, 2015). Although a similar effect to the bottleneck is seen in other types of uni-generational models, such as the naming game (Steels, 1995), the model presented here is novel in that it demonstrates the impact of bottleneck-like behaviour in a generational-based simulation that explores term-based languages.…”
Section: Discussionmentioning
confidence: 99%